The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/1361-665x/ab9e0a
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and experiment of the magnetorheological seat suspension with a seated occupant in both shock and vibration occasions

Abstract: The aim of the present work is to develop an magnetorheological (MR) seat suspension for military vehicles to mitigate dynamic responses of seated occupant in both shock and vibration occasions. The main components of the MR seat suspension are tested and modelled. Subsequently, a mathematical model incorporating the MR seat and a seated occupant is established. The vibration and shock simulations based on the established model are carried out, and the results indicate that the proposed MR seat suspension can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Jiang et al designed a MR seat suspension for military vehicles. The experimental tests showed that it can effectively reduce the human response to shock and vibration [27]. Sun et al introduced a rotary MRD into a seat suspension, which possesses the advantages of less MR fluid and lower cost than that of linear MRD [26].…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al designed a MR seat suspension for military vehicles. The experimental tests showed that it can effectively reduce the human response to shock and vibration [27]. Sun et al introduced a rotary MRD into a seat suspension, which possesses the advantages of less MR fluid and lower cost than that of linear MRD [26].…”
Section: Introductionmentioning
confidence: 99%
“…The field-dependent pressure drop in the activated region can be controlled by adjusting the applied current to change the magnetic field intensity of the activated region, thereby controlling the mechanical properties of the MRA. The MRA has been widely used in vehicle suspension [7,8], landing gear [9,10], and vibration isolation [11,12] research over the last few decades because of its advantages of continuous and adjustable hydraulic resistance, rapid response, and low power consumption. The MR fluid in the gap is a fully developed unsteady laminar flow for the above applications.…”
Section: Introductionmentioning
confidence: 99%